Common Sage (Salvia officinalis L.) Breeding Studies in Central Anatolian Climatic Conditions - Reyhan Bahtiyarca Bagdat; Nurettin Cinkaya; Kadriye Yuksel Demiray; Cigdem Bozdemir; Emel Cakır (International Journal of Secondary Metabolite)
Salvia officinalis L., Lamiaceae, known as Dalmatian Sage or common sage has been gaining popularity in food and drug industries worldwide, recently. Even the existence of many sage species on the World, the genus officinalis has medicinal common use. Indigestion and inflammation disorders, excessive sweating, including that associated with peri-menopause; relief of pressure spots that result from the use of a prosthesis; and as a flavoring for foods are the main areas where the plant is mainly consumed. Sage essential oil has also been employed as a fragrance in soaps and perfumes. Wide adaptability and non-selective climatic requirements of the plats made it possible to receive high biomass, and several harvests during the same plantation period. Present study was conducted in Ankara, during the successive two growing season of 2014 and 2016. Thirty-three spontaneous hybrid common sage lines (Salvia officinalis L.) were evaluated regarding their biomass production and essential oil characteristics employing 4 different standard sage cultivars and lines. Following yield parameters were recorded as; the plant height was ranged 50.3 to 97.5 cm, canopy diameter was 36.0 to 95.0 cm, fresh herb yield was changed 59.9 to 593.4 g/per plant, drug herb yield was 12.6 to 183.9 g/per plant, drug leaf yield was 16.1 to 74.5 g/per plant and the leaf ratio was around 53.42-67.01%. The essential oil ratio was changed between 0.88 and 2.42%. All the yield parameters of the lines were found statistically significant. α-thujone, 1.8 cineole, borneol, camphor, β-thujone, camphene and viridiflorol were the main components. More than ten lines had less than 20% of α-thujone. Phytophtora cryptogea was identified as devastating pathogen confirmed by molecular characterization.